Novel thermoplastic vulcanizates by selectively dynamic cross-linking based on PVDF/PTW blends: structure and property. Issue 2 (22nd January 2020) - Bai, Huiyu; Lu, Jiajun; Li, Bo; Zhang, Shengwen; Wang, Wei; Ma, Piming; Dong, Weifu
ABSTRACT: A novel thermoplastic vulcanizate (TPV) based on poly (vinylidene fluoride)/poly (ethylene–butylacrylate–glycidyl methacrylate) (PVDF/PTW) (30/70 w/w) blends has been fabricated by dynamic vulcanization due to selective cross-linking of PTW by adding small amount of 3-(2-Aminoethylamino) propyldimethoxymethylsilane (KH602). The blends with KH602 had the solid-like behavior at low frequency and enhanced viscosities and dynamic modulus. The TPV exhibited a quasi co-continuous morphology with PVDF dispersed in PTW matrix, which was different from that of PVDF/PTW blend, exhibiting phase-separated morphology with PVDF dispersed in unvulcanized PTW matrix. The resulted TPVs displayed excellent mechanical properties, and excellent strain recovery, which will be a promising coating material, especially wire and cable applications. Graphical Abstract: